Inteligência artificial no Direito brasileiro: o projeto ALEI do Tribunal Regional Federal da 1a Região e a otimização do sistema de justiça - MIRANDA, Márcia Lúcia Lopes de (2022)
This research brings an approach on the ALEI Project (Intelligent Legal Analysis) instituted within the scope of the Federal Regional Court of the 1st Region (TRF1), as an artificial intelligence system aimed at the automation of second instance procedural stages, through the creation of machine learning models for the analysis of the appeals received by TRF1 and the optimization of the various procedural stages involved. In view of the functionalities of the digital tool and its wide application in Law, this study initially analyzes the general aspects of Artificial Intelligence (AI) and its historical evolution, highlighting it as a support mechanism for the Brazilian justice system, especially since the implementation of the electronic process. It goes on to examine, as a central theme, the ALEI project and its peculiarities, in light of specific regulations and other important subsidies to the research, emphasizing also the academic-institutional partnership signed between TRF1 and the University of Brasilia (UnB), for the development of the project. The main objective is to identify the positive impact of technology on TRF1 and its effects on the Brazilian justice system. To this end, from the methodological point of view, the research is qualitative in nature, with a deductive method of approach, using, as research techniques, the bibliographic and documentary, with emphasis on the normative acts of the target institution (TRF1) and interviews with the then manager of the ALEI Project and the Chief of Legal Counsel of the pilot office (TRF1), as well as documents intrinsic to the project and other subsidies, such as news and scientific articles.